Tennis Injury: Analysis and Preventions Actions among National Junior Tennis Athlete - Budi, Didik Rilastiyo; Agustan, Boby; Listiandi, Arfin Deri; Hidayat, Rohman; Hanief, Yulingga Nanda; Qohhar, Wildan; Setiawan, Anang; Nur, Lutfi (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to analyze the level of injury happens among national junior tennis athlete, so that the injury preventive actions can be conducted by recommending exercise programs, number of matches as well as the recovery process. Research methodology applied was Ex-spostfacto study with research approach through observation and interview. Further, the research instruments referred to Joshua et. al (2015) and Kekelesi et. al. (2020) which classifies the tennis injuries into some parts such as shoulder, hand and wrist, elbow, back, hip, thighbone, and ankle as well. Sample of the research used was all the national junior tennis athletes with the age range of 12-18 years old who joined National Tennis Tournament “Totalindo” in total 117 athletes with 73 male, and 44 for female athletes. The analysis and processing of data applied was Ms. Excel application for finding the profiles and the type of injury that whole junior athletes suffered from. Research result proved that the record of injury level happens among national junior tennis athletes in the age range 12-18 was high because there were 156 injury cases from 117 total sample used. In detail, 89 injury cases happened to male athletes and 67 cases to the female. In order to decrease the risk for experiencing the injury, so fundamental movement and multilateral training are highly recommended for junior athletes with age range 12-14 during the training programs. Meanwhile, for those in age range 16-18 can be applied such a proper programs dealing with physical training, techniques, strategies, mentality, and also the recovery programs can boost the athletes to grab more achievements.